2023
DOI: 10.1002/advs.202203423
|View full text |Cite
|
Sign up to set email alerts
|

MYH10 Combines with MYH9 to Recruit USP45 by Deubiquitinating Snail and Promotes Serous Ovarian Cancer Carcinogenesis, Progression, and Cisplatin Resistance

Abstract: The poor prognosis of serous ovarian cancer (SOC) is due to its high invasive capacity and cisplatin resistance of SOC cells, whereas the molecular mechanisms remain poorly understood. In the present study, the expression and function of non‐muscle myosin heavy chain IIB (MYH10) in SOC are identified by immunohistochemistry, in vitro, and in vivo studies, respectively. The mechanism of MYH10 is demonstrated by co‐immunoprecipitation, GST pull‐down, confocal laser assays, and so on. The results show that the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…MYH10 was identified as a protein partner of BlncAD1 , and this relationship was supported by the results of RNA pull-down, RIP, and colocalization assays. Previous studies have shown that MYH10 knockdown inhibits the proliferation of SOC cells . It has been reported that MYH10 is a novel regulator of adipogenesis, and knockdown of MYH10 leads to impaired adipogenesis in preadipocytes .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…MYH10 was identified as a protein partner of BlncAD1 , and this relationship was supported by the results of RNA pull-down, RIP, and colocalization assays. Previous studies have shown that MYH10 knockdown inhibits the proliferation of SOC cells . It has been reported that MYH10 is a novel regulator of adipogenesis, and knockdown of MYH10 leads to impaired adipogenesis in preadipocytes .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that MYH10 knockdown inhibits the proliferation of SOC cells. 32 It has been reported that MYH10 is a novel regulator of adipogenesis, and knockdown of MYH10 leads to impaired adipogenesis in preadipocytes. 24 Our results revealed that knockdown of MYH10 inhibited the proliferation and differentiation of bovine preadipocytes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, a hepatocellular carcinoma (HCC) research study has reported that genomic depletion at the MYH10 locus (17p13.1) is significantly correlated with decreased OS ( p = 0.017, HR = 1.55) and DFS ( p = 0.003, HR = 1.59) and that the downregulation of MYH10 can promote HCC metastasis [ 68 ]. A serous ovarian cancer research study has reported that MYH10 expression is associated with intraperitoneal metastasis ( p < 0.0001) and intestinal metastasis ( p = 0.0281) [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that the high expression of FLNA can lead to low survival rate and migration and invasion energy of GC cells[ 69 ]. Additionally, the disulfidptosis-related gene MYH10 may be related to the occurrence, development, and drug resistance of ovarian cancer[ 70 ], but its role in GC requires further exploration. Moreover, previous studies have revealed that DSTN increases the colony formation and migration ability of tumor cells when highly expressed[ 71 ], although its relationship with GC prognosis requires further study.…”
Section: Discussionmentioning
confidence: 99%